THROMBOPROPHYLAXIS IMPACT IN PATIENTS UNDERGOING MAJOR ORTHOPEDIC SURGERY IN SUDAN - Aldosh, Abubaker; Hamad, Kholoud; Hashim, Ali; Mohammed, Aziza; Babiker, Osman; Saeed, Ali Awadallah; Mousnad, Mohamed A. (Universal Journal of Pharmaceutical Research, 2020)
Objective: Venous thromboembolism is an important complication of major orthopedic surgery. The aim of present study was to investigate the efficacy of the currently used thromboprophylaxis protocol, determine the incidence of VTE post operatively and the risk factors behind it in patients undergoing major orthopedic surgery. Methods: A retrospective descriptive study for 403 patients underwent major orthopedic surgery from July 2013 to July 2014 in main hospitals in Khartoum state where major orthopedic surgery performed. Data were collected using observation checklist and analyzed using SPSS version 22 to study the association between the type of surgery, patient’s risk factors, choice and duration of thromboprophylaxis and development of VTE after major orthopedic surgery. Results: Total 403 patients were incorporated the study, 2.73% were diagnosed with DVT developed within 5 days post operatively. 1.64% of the patients not received any type of thromboprophylaxis, 0.27% wore compression stocking. Pharmacological methods were used in the rest of the patients, 96.72% administered to them enoxaparine. 75.95% of the patients presented with one or more than one risk factors for VTE other than the orthopedic surgery. 4% of patients received thromboprophylaxis for more than 14 days while 96% received it for 3-5 days. The incidence of DVT was higher in diabetic patients (p- value= 0.03) and hypertensive (p- value= 0.046) who aged ≥60 years. Conclusion: Results showed that VTE was a significant complication of major orthopedic surgery, despite the use of thromboprophylaxis and the incidence was 2.73% in our study. Peer Review History: Received 8 April 2020; Revised 7 May; Accepted 24 June; Available online 15 July 2020 Academic Editor: Essam Mohamed Eissa , Beni-Suef University, Egypt, dressamceutics@yahoo.com Reviewer(s) detail: Dr. Michael Otakhor Erhunmwunse , St. Philomena Catholic Hospital, Nigeria, dedoctor4life@gmail.com Francesco Ferrara, USL Umbria , Pharmacy Department, Perugia, Italy, francesco.ferrara@uslumbria1.it